Doppler ultrasound of the pulmonary arterial trunk in the prediction of fetal lung maturity - Huamán Guerrero, Moisés (2015)
Objectives: To determine Doppler fetal pulmonary arterial trunk acceleration/deceleration times (AT/DT) in relation with gestational age, and if there would be a value of such index that would indicate pulmonary maturity with acceptable predictability. Design: Prospective and descriptive study.Setting: Instituto Latinoamericano de Salud Reproductiva, Lima, Peru, a teaching institution. Participants: Healthy women with single pregnancy. Methods: During 2007 and 2008, 79 pregnant women with 26 to 39 weeks healthy singleton pregnancies were studied. AT and DT mean values were measured in the fetal pulmonary arterial trunk using Doppler ultrasound and related to gestational age (GA). Results had statistical analysis to determine a cut value for pulmonary maturity, considering fetuses over 37 weeks have pulmonary maturity and none of the newborns studied had respiratory distress. Main outcome measures: Acceleration time/deceleration time (TA/TD) measured at the pulmonary artery trunk by Doppler ultrasound. Results: AT and DT Doppler fetal pulmonary artery trunk mean values showed a progressive increase with gestational age. There was AT/DT significant difference between less than 37 weeks and 37 weeks or more gestational age (AT/DT index ≥ 0,57, p=0,02). Thus, 0,57 or higher values would be a protection indicator of fetal pulmonary maturity (OR= 0,242; 95% CI 0,071-0,827) and below 0,57 would be a risk indicator of fetal pulmonary immaturity (OR=4,127; 95% CI 1,209-14,088) (GA <32-36 weeks 78,8% vs. GA >37 weeks 47,4%). Conclusions: Doppler ultrasound measurement of AT/DT index in the fetal pulmonary artery trunk would represent a non-invasive, reproducible and reliable test for fetal pulmonary maturity evaluation. Further studies are needed to determine the predictive value of this test in complicated pregnancies, comparing results with those obtained from amniotic fluid tests.